Changes in mental health problems and access to mental health care among US adolescents before and during the COVID-19 pandemic: results from the national survey of children’s health - Lei Xu; Wenhua Lu; Divya Talwar; Sarah B. Maness; Huabin Luo (BMC Public Health)
Abstract Objectives The increase in mental health problems among adolescents is a vital public health issue in the United States. It is crucial to understand how this concerning trend was exacerbated by the COVID-19 pandemic. Using a national representative sample, we assessed the impact of COVID-19 on mental health and access to mental health care access among adolescents. Methods Data was extracted from the 2019 and 2022 National Survey of Children’s Health (NSCH), an annually collected survey on the health and well-being of adolescents in the U.S. A total of 31,258 adolescents ages 12–17 years were included in this analysis. The two primary outcomes were reports of (1) mental health problems (yes/no) and (2) mental healthcare access (yes/no) in the past 12 months. We ran separate multiple logistic regression models to assess the changes in mental health problems and access to mental health care from 2019 to 2022. Results Overall, our results indicated a higher prevalence of adolescent mental health problems reported in 2022 (30.6% 95% CI: 29.4–31.9%) than in 2019 (26.9%, 25.2–28.6%) (p = 0.001). Results of a regression model showed that adolescents who identified as non-Hispanic Black, had parents with higher education levels and who experienced childhood adverse events were more likely to have parent-reported mental health problems (all p < 0.001). Results of the regression model on access to mental health care indicated that adolescent girls were more likely to have access to mental health care than boys (AOR = 2.15, 95% CI:1.80–2.58). Adolescents from families with higher income, with insurance coverage, living in neighborhoods with more amenities, urban areas, and those who experienced adverse childhood events were all more likely to have accessed mental health care than their counterparts. (all p < 0.05). Conclusions We found the prevalence of mental health problems in adolescents increased while the prevalence of access to mental health care decreased from 2019 to 2022, before and during the COVID-19 pandemic. This trend should be closely monitored. And special efforts are needed to help those adolescents who are affected.